Collection and remanufacturing channels selection under a product take-back regulation with remanufacturing target - Kushwaha S.; Chan F.T.S.; Chakraborty K.; Pratap S. (My University, 2025)
Consider a product take-back regulation with remanufacturing target imposed on a manufacturer. The manufacturer is responsible for regulation compliance by remanufacturing the product collected from multiple geographic regions. The channel alternatives for the manufacturer are 1) regional third-party collection firms, 2) regional third-party collection-remanufacturing firms, 3) a third-party firm for remanufacturing, 4) in-house collection, and 5) in-house remanufacturing. The paper proposes a mixed-integer linear programming problem (MILP) formulation for the manufacturer to select a combination of these channels to maximise the profit over a finite planning horizon. The decision model has the number of used products, remanufacturing approach, heterogeneity in the quality of returned products, and the remanufacturing target as constraints. We conduct numerical analysis using field study data for 200 litres of mild-steel drums in India to draw managerial insights. The vital suggestions and insights are as follows. 1) Regulators to impose incremental targets considering the current optimum level of remanufacturing. 2) A comprehensive remanufacturing target covering multi-region/market to discourage manufacturers from evading behaviour. 3) Managers to assist regional firms in increasing the recovery rate of products that can collect and remanufacture. 5) Manufacturers to remanufacture products during the decline stage of product life cycle (PLC) for higher profits. © 2022 Informa UK Limited, trading as Taylor & Francis Group.